MODERN WAYS TO INCREASE THE ECONOMIC ACTIVITY OF YOUNG ENTREPRENEURS IN REGIONAL SOCIETY (TAMADDUN NURI JURNALI, 2025)
This article analyzes the role and responsibilities of local authorities in the development of youth entrepreneurship. In the current socio-economic conditions, mechanisms for increasing the activity of young people in the business sector, supporting them, and the participation of the municipal government system in this process are revealed. The effectiveness of state and local programs aimed at stimulating entrepreneurship in regional society, existing problems and ways to eliminate them are also considered.